Policy Implementation: Challenges in Developing Countries like Nepal - Shahi, Hari Bhakta (Innovative Research Journal, 2023)
Policy formulation is directly associated to policy implementation. Policy implementation is action of plan, program, rules and regulation into real ground. Policy implementation in developing countries is weak policy due to poverty, pseudo agenda, weak state, incomplete cycle, unethical behavior, bureaucratic culture, foreign influence, feudal culture and party conflict. Thus, policy implementation is complex task in developing country like Nepal. There are many issues being raised in developing countries like Nepal for policy implementation. Some people blame the government for not implementing policies whereas government blame opposition parties for blocking the policy implementation.